2012
DOI: 10.1021/ie301656n
|View full text |Cite
|
Sign up to set email alerts
|

Local Composition for a Binary Mixture of Particles on a Three-Dimensional Ising Lattice

Abstract: Results from Monte Carlo (MC) simulations are reported for a binary mixture of particles A and B placed at the nodes of a three-dimensional cubic Ising lattice, with pairwise nearest neighbor interactions between species i and j, E ij . The local composition is studied as a function of composition and of the value of the interchange energy (δ = 2E AB – E AA – E BB). The MC results are used to assess the accuracy of analytical theories proposed in the literature as a function of the interchange energy. The loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2013
2013
2013
2013

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(10 citation statements)
references
References 24 publications
2
8
0
Order By: Relevance
“…The deviation becomes very large for Δ values outside the range of −0.5 to 0.5. 22 The present study in 1D provides insight into a model 18,19 proposed for the approximate determination of the local composition. It was developed as an extension of the 1D Ono− Kondo equation for adsorption to various types of systems in higher dimensions.…”
Section: ■ Conclusionmentioning
confidence: 80%
See 4 more Smart Citations
“…The deviation becomes very large for Δ values outside the range of −0.5 to 0.5. 22 The present study in 1D provides insight into a model 18,19 proposed for the approximate determination of the local composition. It was developed as an extension of the 1D Ono− Kondo equation for adsorption to various types of systems in higher dimensions.…”
Section: ■ Conclusionmentioning
confidence: 80%
“…It has been found that the result from the QC theory for the first-neighbor composition, x 1 , is exact in 1D, as expected. 27 This is not true in 2D (results not shown) and in 3D, 22 in which case the QC formula overestimates the value of x 1 for negative values of Δ, and vice versa for Δ > 0. The deviation becomes very large for Δ values outside the range of −0.5 to 0.5.…”
Section: ■ Conclusionmentioning
confidence: 94%
See 3 more Smart Citations